Alveolar Bone Thickness around Anterior Teeth in Different Classifications of Malocclusion: A Systematic Review - Nur Masita Silviana (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Considering the alveolar bone thickness (ABT) in orthodontic treatment needs special attention. The movement of teeth depends on the mechanism of bone remodeling and tissue response to orthodontic forces to evaluate ABT of the maxillary and mandibular anterior teeth in various types of malocclusion. Methods: Only prospective original articles reporting ABT in subjects who have not undergone orthodontic treatment were selected. A total of 10 studies met the eligible criteria. Most all studies measured the thickness using CBCT. ABT on the labial side of the lower anterior teeth in the class I malocclusion group was thicker than in class II. The lingual side of the apical region of the mandibular incisors was lower in the class III group than in class I or II. ABT of the maxillary teeth on the labial surface showed no significant difference among the groups, whereas the palatal side of normal occlusion had a wider bone thickness. The inclination of the upper and lower anterior teeth was influenced by differences in the skeletal malocclusion pattern, which affected the thickness of the bone. Fenestration was more common in class II malocclusion. The results showed that ABT around anterior teeth varied according to the different classifications of malocclusion. The inclination of the upper and lower anterior teeth seemed to be influenced by the sagittal discrepancies. The pattern of facial growth also affected the thickness of the bone. Accurate evaluation is very important to prevent iatrogenic risks during orthodontic treatment.